2003
DOI: 10.1108/eb028962
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐organizational Network Resources: Relation to Career Success and Personality

Abstract: The study investigated the relationship of career instrumental and expressive intra‐organizational network resources with extrinsic and intrinsic career success and with the Big‐Five of personality in a sample of 264 white‐collar workers. Total network resources were associated with extrinsic and intrinsic career success above the contribution of human capital, demographics and mentoring received. And instrumental network resources contributed more strongly than expressive network resources to extrinsic career… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
194
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(206 citation statements)
references
References 109 publications
4
194
0
8
Order By: Relevance
“…Mesch (2012) also found that moderate levels of extra curricular food service experience during schooling appeared to be a benefit to graduates, who had greater industry persistence, which was linked to job satisfaction. Having networks of support, both at home and at work is another factor that is linked to subjective career success (Kuijpers et al, 2006;Bozionelos, 2008).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Mesch (2012) also found that moderate levels of extra curricular food service experience during schooling appeared to be a benefit to graduates, who had greater industry persistence, which was linked to job satisfaction. Having networks of support, both at home and at work is another factor that is linked to subjective career success (Kuijpers et al, 2006;Bozionelos, 2008).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Aryee and Chay (1994) found that having a mentor resulted in more job involvement, more organizational commitment, and increased job satisfaction. Joiner, Baartram, and Garreffa (2004) and Bozionelos (2008) also found that having a mentor increases perceived career success. However, even having a network of support, be that informal friendships (Bozionelos, 2008;Iverson & Deery, 1997) or the support of a spouse (Judge et al, 1995) or the wider family (Wang et al, 2011) at home, increases the career success of an individual.…”
Section: Motivational Skillsmentioning
confidence: 99%
“…It argues that the presence of both task and informal interdependence within a team can have negative effects (Flache, 2002;2003). The reason for this is that the different types of interdependence may require conflicting types of behaviour from team members.…”
Section: Social Dependence Mechanismmentioning
confidence: 99%
“…This leads to the situation in which formally interdependent employees are also informally interdependent. Flache (2002;2003) identifies two opposing mechanisms that have been studied in this respect: the social control mechanism and the social dependence mechanism. These mechanisms lead to contrasting hypotheses about the mutual effect of task and informal interdependence on solidarity toward co-workers.…”
Section: Task Interdependence and Informal Interdependencementioning
confidence: 99%
See 1 more Smart Citation